Rediscovery of Utricularia cutleri Steyerm. (Lentibulariaceae) in Rio Grande do Norte, Brazil: Taxonomic Reestablishment, Geographic Distribution, and Notes on Pollen and Bladder-Trap Micromorphology - Guedes, Felipe Martins; Garcia, Gabriel Santos; Araujo, Giselle B. [UNESP]; Coan, Alessandra Ike [UNESP]; Alves, Marccus (Amer Soc Plant Taxonomists, 2019)
The rediscovery of a carnivorous plant, Utricularia cutleri, in a seasonally flooded coastal plain in the Atlantic Forest domain, is here reported. This species was first described in 1952 with a few collections from that time, and since 1989 was considered a synonym of U. viscosa. Combined macro- and micromorphological evidence using SEM analysis is provided to propose its taxonomic reestablishment. Utricularia cutleri was originally known only from the type collection in Ceara state, and here we report two new records from Mato Grosso and Rio Grande do Norte states, in central-western and northeastern Brazil. Updated morphological description, geographic distribution, and conservation status are provided, as well as comparative discussion with U. viscosa. Moreover, an updated identification key to species of Lentibulariaceae from Rio Grande do Norte is also presented.
Keywords: Atlantic Forest; carnivorous plants; pioneer formations; synonym; taxonomy